English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

Let J be Joe's age now
Let L be Luis' age now

Write an equation for now:
J = 4L

Write an equation for 6 years from now:
(J + 6) = 2(L + 6)

Substitute 4L in for J:
4L + 6 = 2L + 12

Group like terms on opposite sides:
2L = 6

Divide both sides by 2:
L = 3

Now plug 3 into J = 4L
J = 4(3)
J = 12

So:
Joe is 12, Luis is 3
(and in six years they will be 18 and 9)

2006-10-04 11:53:56 · answer #1 · answered by Puzzling 7 · 0 0

have L = Luis age and J = Joe's age
J = 4L
J + 6 = 2(L +6)

first plug the first value for J into the second equation:
J + 6 = 2(L +6)
4L + 6 = 2(L +6)
4L + 6 = 2L + 12

subtract 6 and 2L from both sides
2L = 6

L = 3
Luis is 3

plug this into the first equation to find Joe's age:
J = 4L
J = 4(3)
J = 12

Joe is 12

(in 6 years Joe will be 18 and Luis will be 9)

2006-10-04 19:01:10 · answer #2 · answered by Anonymous · 0 0

Joe is 12 years old and Luis is 3 and in 6 years Joe will be 18 and Luis will be 9 years old

2006-10-04 18:57:34 · answer #3 · answered by just anotha chick 4 · 0 0

You should try doing your own homework.

2006-10-04 18:58:43 · answer #4 · answered by Fleecie 1 · 0 0

i need to know

2006-10-04 18:52:15 · answer #5 · answered by surfergirl 5 · 0 0

fedest.com, questions and answers